The Apostle Paul's Pastoral Doctrines of Election and Perseverance in 1 Thessalonians 1-3 - Payne, Matthew (2020)
This essay argues that Paul's doctrines of election and perseverance are contained in the so-called "historical" chapters of 1 Thessalonians (chapters 1-3) in the form of pastoral engagement. This becomes apparent when close attention is paid the way that Paul's perspective on the Thessalonian believers develops in these chapters. Paul believed that the perseverance of believers through trials of persecution without turning from the faith proved that God had elected them. However he only reached this point of conviction with regard to his Thessalonian readers as the last of three successive perspectives, namely: that held during his initial visit with them (P1), that of hearing from a distance about the trials that they suffered (P2), and finally that of hearing of their perseverance in the faith by means of Timothy's firsthand report (P3). Paul correspondingly moved from belief that they were Christians (P1), to uncertainty and anxiety about their salvation (P2), before finally arriving at certainty that they were elect (P3). This progression demonstrates that Paul's approach to pastoral care was grounded in theological convictions about God's ongoing activity among his people for their ultimate salvation, and that Paul's historical narrative is richly theological and ought to be regarded seriously as a source of his theology.
Keywords: Bibel